Damage to lemon tree caused by simulated drift of herbicides - Galon, Leandro (2020)
The use of herbicides, in particular clomazone and glyphosate, applied in isolation or in a tank mix, is very common in rice, soybeans, corn and sugarcane fields and the drift of these herbicides can cause damage in sensitive species grown nearby. The purpose of this work was to evaluate the effects of the simulated drift of clomazone and glyphosate applied in an isolated way or mixed in a spray on lemon tree plants. The experiment was installed in a greenhouse in pots with a capacity of 15 L containing sieved soil and an experimental design of randomized blocks was adopted, arranged in a 3 x 5 factorial scheme, with four replications. Plants with two years of development were used. The treatments tested were, clomazone, glyphosate and both mixed, and the decreasing doses of the recommended commercial product: 100, 75, 50, 25 and 0% to simulate herbicide drift. Was evaluated variables, phytotoxicity at 14, 28, 46 and 100 days after application of treatments; plant height, crown volume, the trunk diameter of the rootstock, trunk diameter of the graft and trunk diameter at the grafting point at 0 and 100 days after application of treatments; and liquid assimilation of CO2 at 10 and 60 days after application of treatments. Among the tested herbicides, the one that presented the highest phytotoxicity and the lowest liquid assimilation of CO2 in lemon tree plants was the glyphosate + clomazone mixture. Increases in trunk diameter of the rootstock, grafting point, graft and crown volume did not show significant effects with simulated drift. The plant height presented a greater reduction with the increase of the herbicide doses, mainly glyphosate. That there are considerable losses in lemon tree plants when herbicide drift occurs, mainly by glyphosate and its mixture with clomazone.